Optical laminate and method for producing the same and use thereof
By using the arithmetic average curvature Spc of the peak apex in the optical laminate to control the anti-glare layer below 1.5 mm-1, and laying a low refractive index layer on it, the existing anti-glare film cannot meet the high-fine display. The problem of high anti-glare needs has achieved high anti-glare and anti-reflective effects.
Patent Information
- Application Number
- CN202080072725.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-17
- Filing Date
- 2020-06-04
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-06-04
AI Technical Summary
The existing anti-glare film cannot meet the high anti-glare requirements of high-fine LCD and organic EL displays, and the low refractive index layer cannot fully follow the concave and convex shape of the anti-glare layer, resulting in a decrease in anti-reflectivity.
By controlling the absolute value of the arithmetic average curvature Spc of the peak apex of the surface to 1.5 mm-1 or less anti-glare layer on at least one side of the light-transmissive substrate, the transmission image clarity of the optical laminate is adjusted to be 85% or less. , thereby improving anti-glare properties, and further layering a low refractive index layer on the anti-glare layer to improve anti-reflectivity.
The effect of improving anti-glare and anti-reflective properties is achieved, while excellent transparency and low haze are enhanced, and the visibility of the display device is enhanced.
Smart Images

Figure BDA0003598633310000241 
Figure BDA0003598633310000251 
Figure BDA0003598633310000252
Abstract
Description
Technical Field
[0001] The present disclosure relates to an optical laminate, a method for manufacturing the optical laminate, and uses thereof. The optical laminate can suppress glare on a display surface of various display devices such as a liquid crystal display (LCD) with a touch panel and an organic electroluminescent (EL) display. Background Art
[0002] Anti-glare films are widely used as films for preventing external scenes from being reflected in the display surface of image display devices such as liquid crystal display devices (LCDs) and organic electroluminescent (EL) displays, and for suppressing glare and improving visibility. In anti-glare films, a concavo-convex shape is formed on the surface to scatter and reflect external light to impart anti-glare properties, and a low-refractive index layer (low-refractive index layer) is further provided on the concavo-convex shape to reduce the luminous reflectance and also reduce the sense of reflection, thereby further improving the anti-glare properties.
[0003] Japanese Patent Gazette No. 2008-58723 (Patent Document 1) discloses an anti-glare film, which is composed of the following parts: an anti-glare layer; and a low refractive index layer, which is formed on at least one side of the anti-glare layer and is composed of a low refractive index resin and hollow silica particles. The anti-glare film has an internal haze of 0 to 1%, a haze of 5 to 6.5%, a transmitted image clarity of 20 to 30%, and a hue of reflected light of a*=0.5 to 1.3 and b*=-2.3 to -0.5.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2008-58723 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] However, conventional anti-glare films such as the anti-glare film disclosed in Patent Document 1 cannot provide high anti-glare properties required for image display devices (equipment) such as LCDs and organic EL displays, which have been increasingly refined in recent years.
[0009] Therefore, an object of the present disclosure is to provide an optical layered body capable of improving anti-glare properties, and a method for producing the same, and use thereof.
[0010] Technical Solution
[0011] When the inventors studied the aspects that the conventional anti-glare film could not provide a high degree of anti-glare property, it was found that, in addition to the inability to reflect a high degree of anti-glare property in the surface unevenness of the conventional anti-glare film, the low refractive index layer stacked on the anti-glare layer could not fully follow the unevenness of the anti-glare layer, and the anti-reflection property was reduced compared to the case where the layer was stacked on a layer without unevenness. The inventors conducted in-depth research to achieve the above technical problem and found that the absolute value of the arithmetic mean curvature Spc of the peak vertex of the surface was 1.5 mm. -1 The present invention has been completed by laminating the following antiglare layer on at least one surface of a light-transmitting substrate and adjusting the transmission image clarity of the optical layered body to 85% or less, thereby improving the antiglare property.
[0012] That is, an optical laminate according to one embodiment of the present disclosure includes: a light-transmitting substrate; and an anti-glare layer, which is laminated on at least one side of the light-transmitting substrate and has a concave-convex shape on the surface, wherein the clarity of a transmission image of the optical laminate measured using a 0.5 mm wide optical comb is 85% or less, and the absolute value of the arithmetic mean curvature Spc of the peak vertex of the surface of the anti-glare layer is 1.5 mm -1 The anti-glare layer may be further laminated with a low refractive index layer. The optical laminate having the low refractive index layer may have a light reflectance of 1.4 or less. The absolute value of the arithmetic mean curvature Spc of the peak vertex of the surface of the low refractive index layer may be 1.5 mm. -1 Or less. Alternatively, the absolute value of the arithmetic mean curvature Spc of the peak apex on the surface of the low refractive index layer is 0.3 to 2 times the absolute value of the arithmetic mean curvature Spc of the peak apex on the surface of the glare layer. Alternatively, the refractive index of the anti-glare layer is 1.53 or less. Alternatively, the refractive index of the low refractive index layer is 1.37 or more. Alternatively, the interface expansion area ratio Sdr on the surface of the anti-glare layer is 0.003% or less. Alternatively, the root mean square slope Sdq on the surface of the anti-glare layer is 0.007 or less. Alternatively, the arithmetic mean height Sa on the surface of the anti-glare layer is 0.03 μm or more. Alternatively, the haze of the optical laminate is 1% or less. Preferably, the anti-glare layer does not contain particles.
[0013] One embodiment of the present disclosure also includes a method for manufacturing an optical laminate, the method comprising: an anti-glare layer forming step, phase separation by wet spinodal decomposition to form a concave-convex shape on the surface. Alternatively, the manufacturing method further includes: a low refractive index layer forming step, laminating the low refractive index layer on the anti-glare layer.
[0014] One embodiment of the present disclosure also includes a display device including the optical laminate. Alternatively, the display device may be an LCD or an organic EL display.
[0015] Beneficial Effects
[0016] In one embodiment of the present disclosure, the absolute value of the arithmetic mean curvature Spc of the peak apex of the surface is 1.5 mm -1 The following anti-glare layer is laminated on at least one side of the light-transmissive substrate, and the transmission image clarity of the optical laminate is adjusted to less than 85%, so that the anti-glare property can be improved. Moreover, the anti-glare layer is also excellent in the followability of the low-refractive index layer. When the low-refractive index layer is laminated in a prescribed method, the low-refractive index layer laminated with high followability can be laminated on the anti-glare layer, so that the anti-reflection property can also be improved, and the anti-glare and anti-reflection properties that are difficult to take into account can be improved at the same time. In addition, the transparency is also excellent, and the haze can also be reduced. Moreover, the anti-reflection property can be improved without excessively increasing the refractive index of the anti-glare layer, so the visibility can also be improved. DETAILED DESCRIPTION
[0017] [Anti-glare layer]
[0018] An optical laminate according to an embodiment of the present disclosure includes an anti-glare layer having an absolute value of an arithmetic mean curvature Spc of a peak vertex of 1.5 mm. -1 The following surface concave and convex shapes.
[0019] The absolute value of the arithmetic mean curvature Spc of the peak apex of the anti-glare layer surface is only 1.5 mm. -1 The following may be used, for example, 0.1 to 1.5 mm -1 , preferably 0.5 to 1.4 mm -1 , more preferably 0.8 to 1.3 mm -1 , more preferably 1 to 1.2 mm -1 If the absolute value of Spc is too large, the followability of the low refractive index layer decreases, and the antireflection property is not improved even if the low refractive index layer is laminated on the antiglare layer.
[0020] The arithmetic mean height Sa of the antiglare layer surface may be 0.03 μm or more, for example, 0.03 to 0.1 μm, preferably 0.04 to 0.09 μm, more preferably 0.05 to 0.08 μm, and further preferably 0.06 to 0.075 μm. If Sa is too small, the antiglare property may be reduced.
[0021] The root mean square slope Sdq of the anti-glare layer surface may be 0.007 or less, for example, 0.001 to 0.007, preferably 0.003 to 0.0068, more preferably 0.005 to 0.0065, and more preferably 0.006 to 0.0063. If Sdq is too large, the followability of the low refractive index layer is reduced, and even if the low refractive index layer is laminated on the anti-glare layer, the anti-reflection property may not be improved.
[0022] The interface expansion area ratio Sdr on the surface of the anti-glare layer can be 0.003% or less, for example, 0.0001 to 0.003%, preferably 0.0005 to 0.0028%, more preferably 0.001 to 0.0025%, more preferably 0.0015 to 0.002%. If Sdr is too large, the followability of the low refractive index layer is reduced, and the anti-reflection property may not be improved even if the low refractive index layer is laminated on the anti-glare layer.
[0023] In one embodiment of the present disclosure, in the concavo-convex shape of the anti-glare layer surface, for Spc having the above-mentioned range, by combining Sa, Sdq and Sdr in the above-mentioned range, the anti-glare property based on the light scattering function and the followability relative to the low refractive index layer can be improved in a well-balanced manner.
[0024] It should be noted that in the present specification and claims, Spc, Sa, Sdq and Sdr of the surface of the antiglare layer and the low refractive index layer described below can be measured in accordance with ISO 25178, and more specifically, can be measured by the method described in the examples described below.
[0025] The refractive index of the anti-glare layer may be 1.53 or less, for example, 1.4 to 1.53, preferably 1.45 to 1.53, more preferably 1.48 to 1.53, and more preferably 1.5 to 1.53. In the present disclosure, even if the refractive index of the anti-glare layer is low, the anti-reflective property can be improved. If the refractive index is too high, the refractive index of the light-transmitting substrate becomes large, and there is a fear that a fringe pattern will be generated by interference of reflected light and visibility will be reduced.
[0026] In addition, in this specification and claims, the refractive index of the antiglare layer and the low refractive index layer described later can be measured in accordance with JIS K7142, and more specifically, can be measured by the method described in the examples described later.
[0027] The antiglare layer may be laminated on at least one side of the light-transmitting substrate described below, but is preferably laminated on one side (only one side) of the substrate layer in view of handleability, mechanical properties, productivity, and the like.
[0028] The thickness (average thickness) of the antiglare layer is, for example, 1 to 20 μm, preferably 1.5 to 10 μm, more preferably 2 to 8 μm, and further preferably 4 to 7 μm.
[0029] In addition, in this specification and claims, the average thickness of each layer can be obtained by measuring at any 10 locations using an optical film thickness meter and calculating the average value.
[0030] The anti-glare layer can be made of any material as long as it has the characteristics of the optical laminate described below. The material constituting the anti-glare layer can be selected from transparent organic materials (thermoplastic resins, thermosetting resins, photocurable resins, etc.) and inorganic materials (glass, ceramics, metals, etc.), but from the perspective of being able to form concavoconvex by wet spinodal decomposition and being easy to form the concavoconvex shape of the surface, it is preferred to include a cured product of a curable composition of a curable resin and a polymer component.
[0031] (Curing resin)
[0032] The curable resin may be any of a thermosetting resin and a photocurable resin, but a photocurable resin is preferred from the viewpoint of productivity, etc. A photocurable resin (photocurable resin precursor component) is a compound that can be cured or crosslinked by active energy rays such as ultraviolet rays and electron beams to form a resin, and can be roughly divided into a fluorine-free photocurable resin and a fluorine-containing photocurable resin.
[0033] The fluorine-free photocurable resin includes monomers and oligomers (or resins, particularly low molecular weight resins).
[0034] Examples of the monomer include: monofunctional monomers [(meth)acrylic monomers such as (meth)acrylate, vinyl monomers such as vinyl pyrrolidone, (meth)acrylates having a bridged hydrocarbon group such as isobornyl (meth)acrylate and adamantyl (meth)acrylate], difunctional monomers [alkylene glycol di(meth)acrylate such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, hexanediol di(meth)acrylate; diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polyoxytetramethylene glycol di(meth)acrylate, etc.] ) alkylene glycol di(meth)acrylate; di(meth)acrylates having a bridged hydrocarbon group such as tricyclodecane dimethanol di(meth)acrylate and adamantane diol di(meth)acrylate], trifunctional or higher multifunctional monomers [glycerol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate and other tri- to hexafunctional monomers, etc.], etc. Among them, multifunctional (meth)acrylates having at least two (meth)acryloyl groups are generally used.
[0035] Examples of the oligomer or resin include (meth)acrylates of bisphenol A-alkylene oxide adducts, epoxy (meth)acrylates [polyfunctional epoxy (meth)acrylates having two or more (meth)acryloyl groups], polyester (meth)acrylates [polyfunctional polyester (meth)acrylates having two or more (meth)acryloyl groups], urethane (meth)acrylates [polyfunctional urethane (meth)acrylates having two or more (meth)acryloyl groups], silicone (meth)acrylates [polyfunctional silicone (meth)acrylates having two or more (meth)acryloyl groups], and (meth)acrylic polymers having polymerizable groups.
[0036] These fluorine-free photocurable resins can be used alone or in combination of two or more. Among them, from the perspective of the mechanical properties of the anti-glare layer, it can be a multifunctional monomer with two or more functions, preferably a multifunctional monomer with three or more functions, and further preferably a tri- to hexa-functional monomer [especially a multifunctional (meth) acrylate with 3 to 6 (meth) acryloyl groups such as pentaerythritol tetra (meth) acrylate], and more preferably a tri- to penta-functional monomer (especially a tetra-functional monomer).
[0037] The fluorine-free photocurable resin preferably contains 50% by mass or more, more preferably 80% by mass or more, and more preferably 90% by mass or more of a difunctional or higher polyfunctional monomer (particularly a tri- to pentafunctional monomer). The fluorine-free curable resin may be only a difunctional or higher polyfunctional monomer.
[0038] The fluorine-containing photocurable resin may be a fluoride that is a monomer or oligomer of the fluorine-free photocurable resin. As the fluorine-containing photocurable resin, for example, fluoroalkyl (meth)acrylates [e.g., perfluorooctylethyl (meth)acrylate, trifluoroethyl (meth)acrylate, etc.], fluoro (poly)alkylene glycol di(meth)acrylates [e.g., fluoroethylene glycol di(meth)acrylate, fluoropolyethylene glycol di(meth)acrylate, fluoropropylene glycol di(meth)acrylate, etc.], fluorine-containing epoxy (meth)acrylates, fluorine-containing urethane (meth)acrylates, etc. The fluorine-containing photocurable resin may also be a commercially available fluorine-based polymerizable leveling agent.
[0039] These fluorine-containing photocurable resins may be used alone or in combination of two or more thereof, among which fluorinated polyether compounds having a (meth)acryloyl group and fluorine-containing urethane (meth)acrylates are preferred, and fluorine-containing and ester-containing urethane (meth)acrylates are particularly preferred.
[0040] The photocurable resin preferably contains at least a fluorine-free photocurable resin, and a combination of a fluorine-free photocurable resin and a fluorine-containing photocurable resin is particularly preferred. The proportion of the fluorine-free photocurable resin in the photocurable resin may be 50% by mass or more, preferably 80% by mass or more, and more preferably 90% by mass or more.
[0041] In the case of combining a fluorine-free photocurable resin with a fluorine-containing photocurable resin, for example, the ratio of the fluorine-containing photocurable resin is 0.1 to 10 parts by mass relative to 100 parts by mass of the fluorine-free photocurable resin, preferably 0.2 to 8 parts by mass, further preferably 0.3 to 6 parts by mass, and more preferably 0.4 to 5 parts by mass. If the ratio of the fluorine-containing photocurable resin is too small, the anti-reflective property may be reduced, and if the ratio is too much, the mechanical properties may be reduced. Surprisingly, in the present disclosure, the surface roughness of the anti-glare layer can be increased by combining a fluorine-containing photocurable resin, which is a fluoride that is generally used as a leveling agent to reduce surface tension. Therefore, by combining the fluorine-containing photocurable resin in an appropriate ratio, it can be combined with a low refractive index layer to form a surface concave-convex shape of an anti-glare layer that can take into account both anti-glare and anti-reflective properties.
[0042] (Polymer component)
[0043] As polymer component, thermoplastic resin is usually used. As thermoplastic resin, as long as transparency is high, the above-mentioned surface concavo-convex shape can be formed by spinodal decomposition and is not particularly limited, for example, exemplified: styrene resin, (methyl) acrylic polymer, organic acid vinyl ester polymer, vinyl ether polymer, halogen-containing resin, polyolefin (including alicyclic polyolefin), polycarbonate, polyester, polyamide, thermoplastic polyurethane, polysulfone resin (polyether sulfone, polysulfone etc.), polyphenylene ether resin (polymer of 2,6-xylenol etc.), cellulose derivative (cellulose ester, cellulose carbamate, cellulose ether etc.), organosilicon resin (polydimethylsiloxane, polymethylphenylsiloxane etc.), rubber or elastomer (diene rubber such as polybutadiene, polyisoprene, styrene-butadiene copolymer, acrylonitrile-butadiene copolymer, acrylic rubber, urethane rubber, silicone rubber etc.) etc.. These thermoplastic resins can be used alone, or two or more can be used in combination. Among these polymer components, a combination of a (meth)acrylic polymer and a polyester is preferred from the viewpoint of facilitating formation of the above-mentioned surface irregularities.
[0044] As the (meth)acrylic polymer, a homopolymer or copolymer of a (meth)acrylic monomer, a copolymer of a (meth)acrylic monomer and a copolymerizable monomer, etc. can be used. Examples of the (meth)acrylic monomer include: (meth)acrylic acid; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. (meth)acrylate C 1-10 Alkyl esters; (meth) aryl acrylates such as (meth) acrylate phenyl; (meth) acrylate hydroxyalkyl esters such as (meth) acrylate hydroxyethyl, (meth) acrylate hydroxypropyl; (meth) acrylate glycidyl; (meth) acrylate N, N-dialkylaminoalkyl (meth) acrylate; (meth) acrylonitrile; (meth) acrylates having alicyclic hydrocarbon groups such as tricyclodecane, etc. Copolymerizable monomers can be exemplified by: the above-mentioned styrene monomers, vinyl ester monomers, maleic anhydride, maleic acid, fumaric acid, etc. These monomers can be used alone or in combination of two or more.
[0045] Examples of the (meth)acrylic polymer include poly(meth)acrylates such as polymethyl(meth)acrylate and polyethyl(meth)acrylate, methyl(meth)acrylate-(meth)acrylic acid copolymers, methyl(meth)acrylate-(meth)acrylic acid ester copolymers, methyl(meth)acrylate-acrylic acid ester copolymers, methyl(meth)acrylate-acrylic acid ester-(meth)acrylic acid copolymers, and methyl(meth)acrylate-styrene copolymers (MS resins, etc.).
[0046] Among these (meth)acrylic polymers, it is preferred to include (meth)acrylic acid C such as methyl (meth)acrylate. 1-6 Polymers of alkyl esters, in particular, comprising acrylic acid C 1-4 Polymers of alkyl esters.
[0047] The glass transition temperature of the (meth)acrylic polymer is, for example, 0 to 200°C, preferably 30 to 200°C, and more preferably 50 to 180°C.
[0048] Examples of polyester include aromatic polyesters using aromatic dicarboxylic acids such as terephthalic acid [polyethylene terephthalate, polybutylene terephthalate, etc. 2-4 Alkylene glycol ester or polynaphthalate C 2-4 Homopolymer polyesters such as alkylene glycol esters, including aromatic acid C 2-4 Alkylene glycol ester units (terephthalic acid C 2-4 Alkylene glycol ester and / or naphthalene dicarboxylic acid C 2-4 alkylene glycol ester unit) as the main component (e.g., 50% by mass or more) of the copolyester, etc. As the copolyester, it includes: 2-4 In the constituent units of alkylene glycol esters, C 2-4 A portion of the alkylene glycol is polyoxyethylene 2-4 Alkylene glycol, C 6-10 Copolyesters in which an alkylene glycol, an alicyclic glycol (cyclohexanedimethanol, hydrogenated bisphenol A, etc.), a glycol having an aromatic ring [9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene having a fluorene side chain, bisphenol A, bisphenol A-alkylene oxide adduct, etc.], etc. are substituted; a portion of an aromatic dicarboxylic acid is replaced by an asymmetric aromatic dicarboxylic acid such as phthalic acid and isophthalic acid, an aliphatic C 6-12 Copolyesters substituted with dicarboxylic acids, etc. Polyesters also include: polyarylate resins, aliphatic polyesters using aliphatic dicarboxylic acids such as adipic acid, homopolymers or copolymers of lactones such as ε-caprolactone. Polyesters may also be modified, and may be urethane-modified polyesters modified with polyester urethane or polyether urethane.
[0049] Among these polyesters, non-crystalline copolyesters (e.g., aromatic acid C 2-4 In view of promoting phase separation by spinodal decomposition, urethane-modified polyesters (particularly urethane-modified aromatic polyesters and urethane-modified copolyesters) are particularly preferred.
[0050] The mass ratio of (meth)acrylic polymer to polyester (particularly urethane-modified polyester) is (meth)acrylic resin / polyester = 90 / 10 to 10 / 90, preferably 80 / 20 to 20 / 80, more preferably 70 / 30 to 30 / 70, and more preferably 60 / 40 to 40 / 60. If the ratio of (meth)acrylic resin is too small, it may be difficult to form the above-mentioned concavo-convex shape, and conversely, if the ratio is too large, the same may occur.
[0051] For example, the ratio of the polymer component to 100 parts by mass of the curable resin can be 10 to 200 parts by mass, preferably 30 to 100 parts by mass, more preferably 40 to 80 parts by mass, and more preferably 50 to 70 parts by mass. If the ratio of the polymer component is too small, it may be difficult to form the concavo-convex shape, and conversely, if the ratio is too large, the same may also occur.
[0052] (Curing agent)
[0053] The curable composition may further include a curing agent according to the type of curable resin. For example, a thermosetting resin may include a curing agent such as an amine or a polycarboxylic acid, and a photocurable resin may include a photopolymerization initiator. As the photopolymerization initiator, conventional components may include, for example, acetophenones or propiophenones, benzyls, benzoins, benzophenones, thioxanthones, acylphosphine oxides, and the like.
[0054] For example, the ratio of the curing agent such as the photopolymerization initiator may be 0.1 to 20 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 1 to 5 parts by mass, based on 100 parts by mass of the curable resin.
[0055] The curable composition may further contain a curing accelerator. For example, the photocurable resin may contain a photocuring accelerator such as tertiary amines (dialkylaminobenzoic acid esters, etc.), phosphine-based photopolymerization accelerators, and the like.
[0056] (Other ingredients)
[0057] In addition to the curable resin, polymer component and curing agent, the curable composition may further include other components. As other components, conventional additives may also be included, for example, coupling agents such as silane coupling agents (for example, silane coupling agents with thiol groups, etc.), leveling agents, stabilizers (antioxidants, ultraviolet absorbers, etc.), surfactants, water-soluble polymers, fillers, crosslinking agents, colorants, flame retardants, lubricants, waxes, preservatives, viscosity modifiers, tackifiers, defoamers, etc.
[0058] For example, the ratio of other components can be selected from the range of about 0.01 to 100 parts by mass, for example, 0.1 to 10 parts by mass (particularly 0.5 to 5 parts by mass), relative to 100 parts by mass of the curable resin.
[0059] In one embodiment of the present disclosure, the curable composition preferably contains substantially no particles, and particularly preferably contains no particles, from the viewpoint of being able to easily form the concavo-convex shape and reducing haze.
[0060] [Low refractive index layer]
[0061] In one embodiment of the present disclosure, a low refractive index layer (anti-reflection layer) may be further laminated on the anti-glare layer. In one embodiment of the present disclosure, the low refractive index layer can be laminated with high followability relative to the concavo-convex shape of the anti-glare layer surface, thereby also improving anti-reflection properties and highly improving anti-glare properties.
[0062] The absolute value of the arithmetic mean curvature Spc of the peak top of the low refractive index layer surface is only 1.5 mm -1 The following may be used, for example, 0.1 to 1.5 mm -1 , preferably 0.3 to 1 mm -1 , more preferably 0.4 to 0.8 mm -1 , more preferably 0.5 to 0.7 mm -1 If the absolute value of Spc is too large, the anti-reflection property may be reduced.
[0063] In one embodiment of the present disclosure, a low refractive index layer with high followability can be formed relative to the concave-convex shape of the anti-glare layer, so the difference between the absolute value of Spc of the anti-glare layer and the absolute value of Spc of the low refractive index layer is small, and the absolute value of Spc of the low refractive index layer can be 0.3 to 2 times, for example, 0.5 to 1.5 times, preferably 0.6 to 1.2 times, further preferably 0.8 to 1.1 times, and more preferably 0.9 to 1 times, relative to the absolute value of Spc of the anti-glare layer.
[0064] The arithmetic mean height Sa of the low refractive index layer surface may be 0.03 μm or more, for example, 0.03 to 0.1 μm, preferably 0.033 to 0.08 μm, more preferably 0.035 to 0.07 μm, and even more preferably 0.038 to 0.05 μm. If Sa is too small, the antireflection property may be reduced.
[0065] The difference between Sa of the anti-glare layer and Sa of the low refractive index layer is also small. Sa of the low refractive index layer can be 0.3 to 2 times, for example 0.5 to 1.5 times, preferably 0.6 to 1.2 times, further preferably 0.8 to 1.1 times, and more preferably 0.9 to 1 times, relative to Sa of the anti-glare layer.
[0066] The root mean square slope Sdq of the low refractive index layer surface may be 0.007 or less, for example, 0.001 to 0.007, preferably 0.002 to 0.006, more preferably 0.0025 to 0.005, and even more preferably 0.003 to 0.004. If Sdq is too large, the antireflection property may be reduced.
[0067] The difference between the Sdq of the anti-glare layer and the Sdq of the low refractive index layer is also small. The Sdq of the low refractive index layer can be 0.3 to 2 times, for example 0.5 to 1.5 times, preferably 0.6 to 1.2 times, further preferably 0.8 to 1.1 times, and more preferably 0.9 to 1 times, relative to the Sdq of the anti-glare layer.
[0068] The interface expansion area ratio Sdr of the low refractive index layer surface may be 0.003% or less, for example 0.0001 to 0.003%, preferably 0.0002 to 0.002%, more preferably 0.0003 to 0.0015%, and even more preferably 0.0005 to 0.001%. If Sdr is too large, the antireflection property may be reduced.
[0069] The difference between the Sdr of the antiglare layer and the Sdr of the low refractive index layer is also small. The Sdr of the low refractive index layer can be 0.2 to 2 times, for example, 0.3 to 1.5 times, preferably 0.5 to 1.2 times, further preferably 0.6 to 1.1 times, and more preferably 0.8 to 1 times, relative to the Sdr of the antiglare layer.
[0070] In one embodiment of the present disclosure, in the concavo-convex shape of the surface of the low refractive index layer, for Spc having the above range, by combining Sa, Sdq and Sdr in the above range, the anti-glare property and anti-reflection property based on the light scattering mechanism can be improved in a well-balanced manner.
[0071] The refractive index of the low refractive index layer may be 1.37 or more, and is not particularly limited as long as it is lower than the refractive index of the anti-glare layer, and is, for example, 1.37 to 1.45, preferably 1.37 to 1.4, more preferably 1.37 to 1.39, and more preferably 1.37 to 1.38. If the refractive index is too high, the antireflection property may be reduced.
[0072] The thickness (average thickness) of the low refractive index layer is, for example, 50 to 300 nm, preferably 60 to 150 nm, more preferably 80 to 120 nm, and further preferably 90 to 110 nm.
[0073] The material of the low refractive index layer is not particularly limited as long as it has a lower refractive index than the antiglare layer and has the above-mentioned properties and the properties of the optical laminate described below, and a conventional low refractive index layer (or antireflection layer) can be used.
[0074] As a conventional low refractive index layer, for example, the low refractive index layer described in Japanese Patent Publication No. 2001-100006, Japanese Patent Publication No. 2008-58723, WO2016 / 039125, etc. can be utilized. The low refractive index layer can be formed by a composition comprising a low refractive index resin, or can be formed by a cured product of a composition comprising a curable resin and a fluorinated compound or a low refractive index inorganic filler.
[0075] Examples of the low refractive index resin include methylpentene resin, diethylene glycol bis(allyl carbonate) resin, polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF) and other fluororesins.
[0076] Examples of the curable resin include the fluorine-free photocurable resins listed as examples in the section of the antiglare layer.
[0077] Examples of the fluorine-containing compound include the fluorine-containing photocurable resins exemplified in the section of the antiglare layer.
[0078] For example, the ratio of the fluorine-containing compound in the composition for forming the low refractive index layer may be 1% by mass or more, for example, 5 to 90% by mass, based on the entire composition.
[0079] As the inorganic filler of low refractive index, for example, filler etc. recorded in Japanese Unexamined Patent Publication No. 2001-100006 can be used, preferably filler of low refractive index such as silicon dioxide, magnesium fluoride, particularly silicon dioxide. Silicon dioxide can be hollow silica recorded in Japanese Unexamined Patent Publication No. 2001-233611, Japanese Unexamined Patent Publication No. 2003-192994 etc. Wherein, from the aspect that can suppress haze rising, improve transparency, preferably hollow silica.
[0080] The number average particle size of the inorganic filler (particularly hollow silica) is 100 nm or less, preferably 80 nm or less (eg, 10 to 80 nm), and more preferably about 20 to 70 nm.
[0081] The proportion of the low-refractive-index inorganic filler (particularly hollow silica) in the composition forming the low-refractive-index layer can be 1% by mass or more relative to the entire composition, for example, 5 to 90% by mass. In addition, the low-refractive-index inorganic filler can be surface-modified using a coupling agent (titanium coupling agent, silane coupling agent). Moreover, the composition containing the low-refractive-index inorganic filler can also contain other inorganic fillers in order to improve the coating strength.
[0082] The composition for forming the low refractive index layer may further contain the curing agent exemplified in the section of the anti-glare layer and conventional additives. The preferred embodiments and proportions are the same as those for the anti-glare layer.
[0083] [Light-transmitting substrate]
[0084] The light-transmitting substrate can be made of any transparent material and can be selected according to the application. It can be an inorganic material such as glass, but in terms of strength and formability, an organic material is generally used. Examples of organic materials include cellulose derivatives, polyesters, polyamides, polyimides, polycarbonates, (meth) acrylic polymers, etc. Among them, cellulose derivatives, polyesters, polycarbonates, etc. are generally used, and cellulose esters, polyesters, and polycarbonates are preferred.
[0085] Examples of cellulose esters include cellulose acetate such as triacetyl cellulose (TAC), cellulose acetate propionate, and cellulose acetate butyrate. 3-4 cellulose acid).
[0086] Examples of the polyester include polyaryl alkylene glycol esters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN).
[0087] Examples of the polycarbonate include bisphenol-type polycarbonates such as bisphenol A polycarbonate.
[0088] Among them, cellulose acetate such as TAC is preferred from the viewpoint of excellent balance among mechanical properties, transparency, optical isotropy, and the like.
[0089] The light-transmitting substrate may contain conventional additives as exemplified in the section of the anti-glare layer. Preferred embodiments and proportions are the same as those for the anti-glare layer.
[0090] The light-transmitting substrate may be a uniaxially or biaxially stretched film, but may be an unstretched film from the viewpoint of low birefringence and excellent optical isotropy.
[0091] The light-transmitting substrate may be subjected to a surface treatment (for example, a corona discharge treatment, a flame treatment, a plasma treatment, an ozone or ultraviolet irradiation treatment, etc.), or may have an adhesion-facilitating layer.
[0092] The thickness (average thickness) of the light-transmitting substrate is, for example, 5 to 2000 μm, preferably 15 to 1000 μm, and more preferably 20 to 500 μm.
[0093] [Characteristics of optical laminate]
[0094] The optical layered body of one embodiment of the present disclosure has a transmission image clarity of 85% or less measured using a 0.5 mm wide optical comb. In the present disclosure, the anti-glare property can be improved by adjusting the transmission image clarity of the optical layered body by having the anti-glare layer surface having the above-mentioned concavo-convex shape.
[0095] The transmission image clarity (0.5 mm wide optical comb) of the optical laminate may be 85% or less, for example 30 to 85%, preferably 50 to 83%, more preferably 60 to 82%, and even more preferably 70 to 80%. If the transmission image clarity is too high, the anti-glare property is reduced.
[0096] Transmitted image clarity is a measure that quantifies the blur and distortion of light transmitted through a film. Transmitted image clarity is a value calculated from the amount of light in the bright and dark parts of the light comb by measuring the transmitted light from the film through a moving light comb. That is, when the film blurs the transmitted light, the image of the slit formed on the light comb becomes coarse, so the amount of light in the transmitted part becomes less than 100%, while on the other hand, light leaks in the non-transmitted part, so it becomes more than 0%. The value C of the transmitted image clarity is defined by the following formula based on the maximum value M of the transmitted light in the transparent part of the light comb and the minimum value m of the transmitted light in the opaque part.
[0097] C(%)=[(Mm) / (M+m)]×100
[0098] That is, the closer the value of C is to 100%, the less blurring of the image caused by the anti-glare film [reference: Suga, Mitamura, Coating Technology, July 1985].
[0099] In addition, in this specification and claims, the transmission image clarity can be measured in accordance with JIS K7105, and specifically, can be measured by the method described in the examples described later.
[0100] In one embodiment of the present disclosure, the optical laminate has excellent transparency. The haze of the optical laminate can be 5% or less (especially 1% or less), for example, 0.01 to 1%, preferably 0.05 to 0.8%, more preferably 0.1 to 0.5%, and more preferably 0.2 to 0.4%. In a preferred embodiment of the present disclosure, despite the low haze, the anti-glare property can be improved.
[0101] The total light transmittance of the optical layered body is, for example, 70% or more (eg, 70 to 100%), preferably 90 to 99%, more preferably 92 to 98%, and even more preferably 93 to 97%. If the total light transmittance is too low, the transparency may be reduced.
[0102] In addition, in this specification and claims, haze and total light transmittance can be measured according to JIS K7136, and specifically, can be measured by the method described in the examples described later.
[0103] The optical laminated body laminated with a low refractive index layer has excellent anti-reflection properties. The optical laminated body laminated with a low refractive index layer has a light reflectance of 1.7 or less when measured from the low refractive index layer side, and is preferably 1.4 or less from the perspective of anti-reflection properties. The preferred range of the light reflectance can be selected from the range of about 0.01 to 1.4, for example, 0.05 to 1.3, preferably 0.1 to 1.2, more preferably 0.2 to 1.1, and more preferably 0.3 to 1. If the light reflectance is too high, visibility is reduced due to reflected light.
[0104] In addition, in this specification and claims, light reflectance can be measured according to JIS Z8722, and specifically, can be measured by the method described in the Examples described later.
[0105] In the optical laminate having the low refractive index layer laminated thereon, the wavelength showing the minimum value of the spectral reflectance is, for example, 380 to 780 nm, preferably 400 to 700 nm, more preferably 450 to 650 nm, and further preferably 500 to 600 nm.
[0106] It should be noted that in the present specification and claims, the spectral reflectance can be measured in accordance with JIS Z8722, and more specifically, can be measured by the method described in the Examples described below.
[0107] The optical layered body may have a polarizing layer, a refractive index adjusting layer, an adhesive layer, etc. as conventional functional layers in addition to the antiglare layer and the low refractive index layer.
[0108] The thickness (average thickness) of the optical layered body is, for example, 3 to 2000 μm, preferably 5 to 1000 μm, and more preferably 10 to 500 μm.
[0109] [Method for producing optical layered body]
[0110] The method for producing the optical laminate may include an anti-glare layer forming step for forming the anti-glare layer having the surface irregularities. The anti-glare layer forming step is not particularly limited as long as the anti-glare layer having the surface irregularities can be formed, and a conventional method may be used.
[0111] As conventional methods, for example, there can be listed: a method of forming a concave-convex shape using particles (for example, a method of forming a convex portion following the shape of the particles, etc.); a method of forming a concave-convex shape on the surface by phase separation through wet spinodal decomposition (a method of causing the resin component of a curable composition containing a resin component capable of phase separation to undergo phase separation and then curing the composition); a method of transferring using a mold having a concave-convex shape on the surface; a method of forming a concave-convex shape by cutting (for example, cutting using a laser, etc.); a method of forming a concave-convex shape by grinding (for example, sandblasting, bead blasting, etc.); a method of forming a concave-convex shape by etching, etc.
[0112] Among these methods, from the perspective of productivity, etc., a method in which phase separation occurs by wet spinodal decomposition to form a concavo-convex shape on the surface is preferred. In the method in which phase separation occurs by wet spinodal decomposition, in the process of evaporating or removing the solvent by drying the liquid phase of a composition containing a resin component capable of phase separation and a solvent, phase separation occurs by spinodal decomposition (wet spinodal decomposition) accompanied by an increase in concentration, thereby forming a target concavo-convex shape (concavo-convex shape based on a phase separation structure) on the surface of the anti-glare layer.
[0113] The combination of resin components that can undergo phase separation may be any of the following combinations: a combination of the photocurable resins listed as examples in the anti-glare layer; a combination of the photocurable resin and the polymer component (thermoplastic resin) listed as examples in the anti-glare layer; a combination of the polymer components, preferably a combination of a curable resin (for example, a combination of a multifunctional (meth)acrylate having 3 to 5 (meth)acryloyl groups and a fluorine-containing photocurable compound, etc.), a (meth)acrylic polymer (for example, polymethyl methacrylate, etc.), and a polyester (for example, urethane-modified polyester, etc.), from the perspective of facilitating the formation of a target concave-convex shape on the surface of the anti-glare layer.
[0114] The solvent used in the wet spinodal decomposition can be selected according to the type and solubility of the resin component, as long as it can at least uniformly dissolve the solid component (for example, photocurable resin, polymer component, curing agent, etc.). As such a solvent, for example, ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.), ethers (dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated hydrocarbons (dichloromethane, dichloroethane, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), water, alcohols (ethanol, isopropanol, butanol, cyclohexanol, etc.), cellosolves [methyl cellosolve, ethyl cellosolve, propylene glycol monomethyl ether (1-methoxy-2-propanol), etc.], cellosolve acetates, sulfoxides (dimethyl sulfoxide, etc.), amides (dimethylformamide, dimethylacetamide, etc.), etc. The solvent may be a mixed solvent. Among these solvents, aliphatic ketones such as methyl ethyl ketone and methyl isobutyl ketone are preferred.
[0115] The concentration of the solute (photocurable resin, polymer component, curing agent, etc.) in the composition can be selected within a range that does not impair castability, coating properties, etc., for example, 1 to 80 mass %, preferably 10 to 70 mass %, more preferably 20 to 50 mass %, and more preferably 30 to 40 mass %.
[0116] As the coating method, conventional methods include, for example, roll coater, air knife coater, blade coater, rod coater, reverse coater, bar coater, comma coater, dip / extrusion coater, die coater, gravure coater, micro gravure coater, screen coater method; dipping method; spray coating method; spin coating method, etc. Among these methods, bar coating method, gravure coating method, etc. are commonly used. It should be noted that, as required, the coating liquid can also be applied multiple times.
[0117] The composition may be dried to evaporate the solvent after being cast or coated. The drying may be natural drying or may be carried out at a temperature selected from a range of about 30 to 200° C. according to the boiling point of the solvent. From the perspective of easily forming a target concavo-convex shape on the surface of the anti-glare layer, the drying is preferably carried out at a temperature of 60 to 100° C., more preferably 70 to 90° C., and more preferably 75 to 85° C.
[0118] After drying, the optical laminate is obtained by curing by light irradiation. The light irradiation can be selected according to the type of photocurable resin, etc., and generally ultraviolet rays, electron beams, etc. can be used. A general light source is generally an ultraviolet irradiation device.
[0119] As the light source, for example, in the case of ultraviolet rays, a Deep UV lamp, a low-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a halogen lamp, a laser light source (a light source such as a helium-cadmium laser or an excimer laser), etc. can be used. The irradiation light quantity (irradiation energy as the cumulative light quantity) varies depending on the thickness of the coating film, and is, for example, 10 to 10000 mJ / cm 2 , preferably 20 to 5000 mJ / cm 2 , more preferably 30 to 3000 mJ / cm 2 If necessary, light irradiation may be performed in an inert gas atmosphere.
[0120] As a method utilizing phase separation, for example, the methods described in Japanese Patent Application Laid-Open Nos. 2007-187746, 2008-225195, 2009-267775, 2011-175601, 2014-85371, 2014-92657, 2014-98771, 2016-161859, and 2017-219622 can also be utilized.
[0121] When the optical layered body has a low refractive index layer, the method for producing the optical layered body further includes: a low refractive index layer forming step of laminating the low refractive index layer on the anti-glare layer.
[0122] As a method for laminating the low refractive index layer, a conventional method can also be used, and a method of applying and drying a coating liquid obtained by dissolving or dispersing a composition forming the low refractive index layer in a solvent can be used. In the case where the composition contains a photocurable resin, the coating liquid can be cured after drying by the same method as the anti-glare layer. The coating method and the drying method are the same as those of the anti-glare layer, including the preferred embodiment.
[0123] As the solvent, the solvent used in the wet spinodal decomposition of the anti-glare layer can be used. Among the solvents, alcohols such as isopropyl alcohol (2-propanol) are preferred.
[0124] The concentration of the solute (resin component, inorganic filler, etc.) in the composition can be selected from the range of about 0.1 to 50 mass % within a range that does not impair the castability, coating properties, etc., and is, for example, 1 to 3 mass %, preferably 1.5 to 3 mass %, further preferably 1.8 to 3 mass %, and more preferably 2 to 3 mass %, from the perspective of easily forming a target concave-convex shape on the surface of the anti-glare layer.
[0125] [Display device]
[0126] The optical laminate has excellent anti-glare properties and can be used in various display devices such as liquid crystal display devices (LCD) and organic EL displays. In particular, it is useful as a high-definition LCD or organic EL display.
[0127] In detail, the LCD may be a reflective LCD that utilizes external light to illuminate a display unit having a liquid crystal box, or a transmissive LCD that has a backlight unit for illuminating the display unit. In a reflective LCD, incident light from the outside may be introduced via the display unit, and the transmitted light of the transmissive display unit may be reflected by a reflective component to illuminate the display unit. In a reflective LCD, the optical stack may be disposed in a light path from the reflective component to the front. For example, the optical stack may be disposed or stacked in front of the display unit (in front of the visible side), etc., and in particular, may also be disposed in front of an LCD having a collimated backlight unit and not having a prism sheet.
[0128] In a transmissive LCD, the backlight unit may also include: a light guide plate (e.g., a light guide plate with a wedge-shaped cross section) for allowing light from a light source (a tubular light source such as a cold cathode tube, a point light source such as a light emitting diode, etc.) to be incident from the side on one side and to be emitted from the front exit surface. In addition, as required, a prism sheet may be provided on the front side of the light guide plate. It should be noted that a reflective member for reflecting light from the light source toward the exit surface is usually provided on the back side of the light guide plate. In such a transmissive LCD, the optical stack may usually be provided in the light path from the light source to the front, for example, the optical stack may be provided or stacked in front of the display unit, etc.
[0129] In an organic EL display, a light-emitting element is formed for each pixel, and the light-emitting element is usually formed on a cathode such as metal / electron injection layer / electron transport layer / light-emitting layer / hole transport layer / hole injection layer / anode such as ITO (Indium tin oxide) / a substrate such as a glass plate or a transparent plastic plate. In an organic EL display, the optical laminate may be arranged in a light path.
[0130] Each solution disclosed in this specification may be combined with any other feature disclosed in this specification.
[0131] Example
[0132] Hereinafter, the present disclosure will be further described in detail based on the examples, but the present disclosure is not limited to these examples. The details of the raw materials and films used in the examples and reference examples, as well as the preparation method of the coating solution are shown below, and the optical laminates obtained in the examples and reference examples are evaluated by the following methods.
[0133] [raw material]
[0134] Acrylic acid polymer: "8KX-077" manufactured by Daesei Fine Chemical Co., Ltd.
[0135] Urethane-modified copolyester resin: "VYLON (registered trademark) UR-3500" manufactured by Toyobo Co., Ltd.
[0136] Pentaerythritol tetraacrylate (PETRA): "PETRA" manufactured by Daicel-Allnex Corporation.
[0137] Fluorine compound having a polymerizable group: "FTERGENT 602A" manufactured by NEOS Corporation.
[0138] Photoinitiator: "Omnirad 184" manufactured by IGM Resins.
[0139] Triacetyl cellulose (TAC) film: “FUJITAC TG60UL” manufactured by FUJI FILM CO., LTD.
[0140] Hollow silica-containing coating agent: "P-5062" manufactured by JGC Catalysts & Chemicals Co., Ltd.
[0141] Coating agent containing acrylic fine particles: "FA-3155M" manufactured by Nippon Kagaku Paint Co., Ltd.
[0142] Clear hard coat agent 1: "FA-3155CLEAR" manufactured by Nippon Kagaku Paint Co., Ltd.
[0143] Clear hard coating agent 2: "Z7503" manufactured by Arakawa Chemical Industries, Ltd.
[0144] [Thickness of anti-glare layer]
[0145] Using an optical film thickness meter, measurement was performed at arbitrary 10 locations in the laminated bodies obtained in Examples and Reference Examples, and the average value was calculated.
[0146] [Surface shape]
[0147] In accordance with ISO 25178, an optical surface roughness meter ("VertScan R5500G" manufactured by Hitachi High-Tech Science Co., Ltd.) was used to measure the arithmetic mean height Sa, root mean square slope Sdq, interface expansion area ratio Sdr, and arithmetic mean curvature Spc of the peak apex of the surface (anti-glare layer surface or anti-reflection layer surface) under the conditions of a scanning range of 2.5 mm square and two scanning times.
[0148] [Haze and total light transmittance]
[0149] The haze meter (HM-150L2, manufactured by Murakami Color Laboratory Co., Ltd.) was used to measure the film in accordance with JIS K7136 so that the surface having the concavo-convex structure faced the light receiving side.
[0150] [Transmission image clarity]
[0151] Using an image measuring instrument (manufactured by SUGA Testing Instruments Co., Ltd., ICM-1T), the film was set so that the film forming direction and the direction of the comb teeth of the optical comb were parallel to each other and the measurement was performed in accordance with JIS K7105. The optical comb width was set to 0.5 mm.
[0152] [Spectral reflectance and light reflectance Y]
[0153] The measurement was performed using a spectrophotometer ("U-3900H" manufactured by Hitachi High-Tech Science Co., Ltd.) in accordance with JIS Z8722. The surface of the film opposite to the antireflection layer was bonded to a commercially available black acrylic plate using an optical paste, and the measurement was performed so as to minimize the influence on the reflection from the back surface.
[0154] [Anti-glare]
[0155] The obtained film was bonded to a commercially available black acrylic plate using an optical paste, and a reflection image when irradiated with a three-wavelength fluorescent lamp was visually confirmed and evaluated based on the following criteria.
[0156] ◎: The reflected image is very blurred, and the boundary between the fluorescent light and the outside is completely indistinguishable.
[0157] ○: The reflected image is blurred, but the boundary between the fluorescent lamp and the outside thereof can be slightly distinguished.
[0158] Δ: The reflected image is less blurred, and the boundary between the fluorescent light and the outside can be roughly distinguished.
[0159] ×: The reflected image is not blurred, and the boundary line between the fluorescent lamp and its outer side can be completely distinguished.
[0160] [Refractive index]
[0161] The refractive index was measured at 407 nm, 633 nm (He-Ne laser) and 826 nm at 23° C. using a refractometer (“Metricon Model 2010 Prism Coupler” manufactured by Metricon) in accordance with JIS K7142, and the refractive index at 589 nm was calculated.
[0162] Example 1
[0163] 26 parts by mass of acrylic polymer, 24 parts by mass of urethane-modified copolyester resin, 82 parts by mass of PETRA, 0.5 parts by mass of fluorine-based compound with polymerizable group, and 1 part by mass of photoinitiator were dissolved in 231 parts by mass of methyl ethyl ketone. After casting the solution onto TAC film using wire rod #14, it was placed in an oven at 90°C for 1 minute to evaporate the solvent and form a coating with a thickness of about 4 μm. Then, the coating was irradiated with ultraviolet light from a high-pressure mercury lamp for about 5 seconds in the atmosphere for UV curing treatment (accumulated light amount of about 100 mJ / cm 2 Irradiation, the same below), to obtain an anti-glare film.
[0164] Example 2
[0165] Using wire rod #5, a solution of 100 parts by mass of a coating agent containing hollow silica and 33 parts by mass of 2-propanol was cast onto the concave-convex surface of the film prepared in Example 1, and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form an anti-reflection layer (low refractive index layer). Then, ultraviolet rays from a high-pressure mercury lamp were irradiated for about 5 seconds in a nitrogen atmosphere, and UV curing treatment was performed to obtain an anti-glare / anti-reflection film. In the range of 380nm to 780nm, the wavelength at which the spectral reflectance shows a minimum value is 561nm.
[0166] Example 3
[0167] 26 parts by mass of acrylic polymer, 24 parts by mass of urethane-modified copolyester resin, 82 parts by mass of PETRA, 0.5 parts by mass of fluorine compound having polymerizable group, and 1 part by mass of photoinitiator were dissolved in 231 parts by mass of methyl ethyl ketone. The solution was cast onto TAC film using wire rod #14, and then placed in an oven at 80°C for 1 minute to evaporate the solvent, forming a coating with a thickness of about 4 μm. Then, the coating was irradiated with ultraviolet rays from a high-pressure mercury lamp for about 5 seconds in the atmosphere for UV curing to obtain an anti-glare film.
[0168] Example 4
[0169] Using wire rod #5, a solution of 100 parts by mass of a coating agent containing hollow silica and 33 parts by mass of 2-propanol was cast onto the concave-convex surface of the film produced in Example 3, and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form an anti-reflection layer. Then, ultraviolet rays from a high-pressure mercury lamp were irradiated for about 5 seconds in a nitrogen atmosphere to perform UV curing to obtain an anti-glare / anti-reflection film. In the range of 380nm to 780nm, the wavelength at which the spectral reflectance shows a minimum value is 558nm.
[0170] Example 5
[0171] 20 parts by mass of acrylic polymer, 24 parts by mass of urethane-modified copolyester resin, 82 parts by mass of PETRA, 0.25 parts by mass of fluorine compound having polymerizable group, and 1 part by mass of photoinitiator were dissolved in 231 parts by mass of methyl ethyl ketone. The solution was cast onto TAC film using wire rod #14, and then placed in an oven at 80°C for 1 minute to evaporate the solvent, forming a coating with a thickness of about 4 μm. Then, the coating was irradiated with ultraviolet rays from a high-pressure mercury lamp for about 5 seconds in the atmosphere for UV curing to obtain an anti-glare film.
[0172] Example 6
[0173] Using wire rod #5, a solution of 100 parts by mass of a coating agent containing hollow silica and 33 parts by mass of 2-propanol was cast onto the concave-convex surface of the film prepared in Example 5, and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form an anti-reflection layer. Then, ultraviolet rays from a high-pressure mercury lamp were irradiated for about 5 seconds in a nitrogen atmosphere to perform UV curing to obtain an anti-glare / anti-reflection film. In the range of 380nm to 780nm, the wavelength at which the spectral reflectance shows a minimum value is 574nm.
[0174] Example 7
[0175] 20 parts by mass of acrylic polymer, 24 parts by mass of urethane-modified copolyester resin, 82 parts by mass of PETRA, 0.1 parts by mass of fluorine compound having polymerizable group, and 1 part by mass of photoinitiator were dissolved in 231 parts by mass of methyl ethyl ketone. The solution was cast onto TAC film using wire rod #14, and then placed in an oven at 70°C for 1 minute to evaporate the solvent, forming a coating with a thickness of about 4 μm. Then, the coating was irradiated with ultraviolet rays from a high-pressure mercury lamp for about 5 seconds in the atmosphere for UV curing to obtain an anti-glare film.
[0176] Example 8
[0177] Using wire rod #5, a solution of 100 parts by mass of a coating agent containing hollow silica and 33 parts by mass of 2-propanol was cast onto the concave-convex surface of the film prepared in Example 7, and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form an anti-reflection layer. Then, ultraviolet rays from a high-pressure mercury lamp were irradiated for about 5 seconds in a nitrogen atmosphere to perform UV curing to obtain an anti-glare / anti-reflection film. In the range of 380nm to 780nm, the wavelength at which the spectral reflectance shows a minimum value is 567nm.
[0178] Example 9
[0179] Using wire rod #5, a solution of 100 parts by mass of a coating agent containing hollow silica and 20 parts by mass of 2-propanol was cast onto the concave-convex surface of the film prepared in Example 7, and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form an anti-reflection layer. Then, ultraviolet rays from a high-pressure mercury lamp were irradiated for about 5 seconds in a nitrogen atmosphere to perform UV curing to obtain an anti-glare / anti-reflection film. In the range of 380nm to 780nm, the wavelength at which the spectral reflectance shows a minimum value is 388nm.
[0180] Example 10
[0181] Using wire rod #5, a solution of 100 parts by mass of a coating agent containing hollow silica and 10 parts by mass of 2-propanol was cast onto the concave-convex surface of the film prepared in Example 7, and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form an anti-reflection layer. Then, ultraviolet rays from a high-pressure mercury lamp were irradiated for about 5 seconds in a nitrogen atmosphere to perform UV curing to obtain an anti-glare / anti-reflection film. In the range of 380nm to 780nm, the wavelength at which the spectral reflectance shows a minimum value is 389nm.
[0182] Reference Example 1
[0183] 27 parts by mass of acrylic polymer, 24 parts by mass of urethane-modified copolyester resin, 151 parts by mass of transparent hard coating agent 2, 0.1 parts by mass of fluorine compound having polymerizable group, and 1 part by mass of photoinitiator were dissolved in 161 parts by mass of methyl ethyl ketone. The solution was cast onto TAC film using wire rod #14, and then placed in an oven at 80°C for 1 minute to evaporate the solvent, thereby forming a coating with a thickness of about 5 μm. Then, the coating was irradiated with ultraviolet rays from a high-pressure mercury lamp for about 5 seconds in the atmosphere for UV curing treatment to obtain an anti-glare film.
[0184] Reference Example 2
[0185] Using wire rod #5, a solution of 100 parts by mass of a coating agent containing hollow silica and 33 parts by mass of 2-propanol was cast onto the concave-convex surface of the film prepared in Reference Example 1, and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form an anti-reflection layer. Then, ultraviolet rays from a high-pressure mercury lamp were irradiated for about 5 seconds in a nitrogen atmosphere to perform UV curing to obtain an anti-glare / anti-reflection film. In the range of 380nm to 780nm, the wavelength at which the spectral reflectance shows a minimum value is 554nm.
[0186] Reference Example 3
[0187] 50 parts by mass of a coating agent containing acrylic microparticles, 100 parts by mass of a transparent hard coating agent 1, and 0.1 parts by mass of a fluorine compound having a polymerizable group were mixed. The solution was cast onto a TAC film using a wire rod #8, and then placed in an oven at 80°C for 1 minute to evaporate the solvent, thereby forming a coating having a thickness of about 5 μm. The coating was then irradiated with ultraviolet light from a high-pressure mercury lamp for about 5 seconds in the atmosphere for UV curing to obtain an anti-glare film.
[0188] Reference Example 4
[0189] Using wire rod #5, a solution of 100 parts by mass of a coating agent containing hollow silica and 33 parts by mass of 2-propanol was cast onto the concave-convex surface of the film prepared in Reference Example 3, and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form an anti-reflection layer. Then, ultraviolet rays from a high-pressure mercury lamp were irradiated for about 5 seconds in a nitrogen atmosphere, and UV curing was performed to obtain an anti-glare / anti-reflection film. In the range of 380nm to 780nm, the wavelength at which the spectral reflectance shows a minimum value is 585nm.
[0190] Reference Example 5
[0191] 50 parts by mass of a coating agent containing acrylic microparticles, 50 parts by mass of a transparent hard coating agent 1, and 0.1 parts by mass of a fluorine compound having a polymerizable group were mixed. The solution was cast onto a TAC film using a wire rod #8, and then placed in an oven at 80°C for 1 minute to evaporate the solvent, thereby forming a coating having a thickness of about 5 μm. Then, the coating was irradiated with ultraviolet rays from a high-pressure mercury lamp for about 5 seconds in the atmosphere for UV curing to obtain an anti-glare film.
[0192] Reference Example 6
[0193] Using wire rod #5, a solution of 100 parts by mass of a coating agent containing hollow silica and 33 parts by mass of 2-propanol was cast onto the concave-convex surface of the film prepared in Reference Example 5, and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form an anti-reflection layer. Then, ultraviolet rays from a high-pressure mercury lamp were irradiated for about 5 seconds in a nitrogen atmosphere to perform UV curing to obtain an anti-glare / anti-reflection film. In the range of 380nm to 780nm, the wavelength at which the spectral reflectance shows a minimum value is 508nm.
[0194] Reference Example 7
[0195] 100 parts by mass of the transparent hard coating agent 1 was mixed with 0.1 parts by mass of a fluorine compound having a polymerizable group. The solution was cast onto a TAC film using a wire rod #8, and then placed in an oven at 80°C for 1 minute to evaporate the solvent, thereby forming a coating having a thickness of about 5 μm. The coating was then irradiated with ultraviolet light from a high-pressure mercury lamp for about 5 seconds in the atmosphere for UV curing to obtain an anti-glare film.
[0196] Reference Example 8
[0197] Using wire rod #4, a solution of 100 parts by mass of a coating agent containing hollow silica and 11 parts by mass of 2-propanol was cast onto the concave-convex surface of the film prepared in Reference Example 7, and then placed in an oven at 80°C for 1 minute to evaporate the solvent and form an anti-reflection layer. Then, ultraviolet rays from a high-pressure mercury lamp were irradiated for about 5 seconds in a nitrogen atmosphere to perform UV curing to obtain an anti-glare / anti-reflection film. In the range of 380nm to 780nm, the wavelength at which the spectral reflectance shows a minimum value is 531nm.
[0198] The evaluation results of the antiglare films and antiglare / antireflection films obtained in Examples 1 to 10 are shown in Table 1, and the evaluation results of the antiglare films and antiglare / antireflection films obtained in Reference Examples 1 to 8 are shown in Table 2.
[0199] [Table 1]
[0200]
[0201]
[0202] [Table 2]
[0203]
[0204] The results in Table 1 clearly show that the antiglare films and antiglare / antireflection films of Examples have high antiglare properties and low haze. The antiglare / antireflection films of Examples 2, 4, 6, and 8 to 9 also have low light reflectance.
[0205] Industrial Applicability
[0206] The optical laminate according to one embodiment of the present disclosure can be used as an anti-glare film or protective film on the surface of various display devices, such as liquid crystal display devices (LCD), cathode tube display devices, organic or inorganic electroluminescent (EL) displays, field emission displays (FED), surface conduction electron emission displays (SED), rear projection television displays, etc., and is particularly suitable for applications requiring high-definition images, such as gaming devices, smart phones, personal computers (PCs) (tablet PCs, notebook or laptop PCs, desktop PCs, etc.), pointing devices for computers such as drawing tablets, televisions, and other display devices.
Claims
1. An optical laminate, comprising: Light-transmitting substrate; and an anti-glare layer, which is laminated on at least one side of the light-transmitting substrate and has a concavo-convex shape on the surface, The optical laminate has a transmission image clarity of 85% or less measured using a 0.5 mm wide optical comb, The absolute value of the arithmetic mean curvature Spc of the peak apex of the anti-glare layer surface is 0.5 to 1.5 mm -1 .
2. The optical layered body according to claim 1, wherein: A low refractive index layer is further laminated on the anti-glare layer, and the optical layered body has a light reflectance of 1.4 or less.
3. The optical laminate according to claim 2, wherein: The absolute value of the arithmetic mean curvature Spc of the peak vertex of the surface of the low refractive index layer is 1.5 mm -1 the following.
4. The optical layered body according to claim 2 or 3, wherein: The absolute value of the arithmetic mean curvature Spc of the peak apex of the surface of the low refractive index layer is 0.3 to 2 times the absolute value of the arithmetic mean curvature Spc of the peak apex of the surface of the anti-glare layer.
5. The optical layered body according to claim 2 or 3, wherein: The refractive index of the anti-glare layer is 1.53 or less, and the refractive index of the low refractive index layer is 1.37 or more.
6. The optical layered body according to any one of claims 1 to 3, wherein The interface expansion area ratio Sdr of the surface of the anti-glare layer is 0.003% or less.
7. The optical layered body according to any one of claims 1 to 3, wherein The root mean square slope Sdq of the surface of the anti-glare layer is less than or equal to 0.
007.
8. The optical layered body according to any one of claims 1 to 3, wherein The arithmetic mean height Sa of the surface of the anti-glare layer is greater than or equal to 0.03 μm.
9. The optical layered body according to any one of claims 1 to 3, wherein The haze is 1% or less.
10. The optical layered body according to any one of claims 1 to 3, wherein The anti-glare layer does not contain particles.
11. A method for producing an optical layered body according to any one of claims 1 to 10, comprising: In the anti-glare layer forming step, phase separation occurs by wet spinodal decomposition to form a concavo-convex shape on the surface.
12. The manufacturing method according to claim 11, further comprising: The low refractive index layer forming step is to laminate the low refractive index layer on the anti-glare layer. 13 . A display device comprising the optical layered body according to claim 1 .
14. The display device according to claim 13, wherein: The display device is a liquid crystal display device or an organic EL display.
Citation Information
Patent Citations
Antidazzle antireflection film and image display device
JP2001100006A
Silica-based microparticle, method for producing dispersion with the same, and base material with coating film
JP2001233611A
Coating liquid for forming transparent electroconductive coating film, substrate with transparent electroconductive coating film and display device
JP2003192994A
Antiglare film and method for manufacturing the same
JP2007187746A
Anti-glare film and liquid crystal display apparatus
JP2008058723A